Combined Deep Brain Stimulation of Subthalamic Nucleus and Ventral Intermediate Thalamic Nucleus in Tremor‐Dominant Parkinson's Disease Using a Parietal Approach. Issue 4 (19th March 2019) - Neudorfer, Clemens; Hinzke, Markus; Hunsche, Stefan; El Majdoub, Faycal; Lozano, Andres; Maarouf, Mohammad
Abstract : Objectives: Despite its efficacy in tremor‐suppression, the ventral intermediate thalamic (VIM) nucleus has largely been neglected in deep brain stimulation (DBS) for tremor‐dominant Parkinson's disease (tdPD). The employment of a parietal approach, however, allows stimulation of VIM and subthalamic nucleus (STN) using one trajectory only and thus constitutes a promising alternative to existing strategies. In the present study, we investigate safety and efficacy of combined lead implantation and stimulation of STN and VIM using a parietal approach. Materials and Methods: Retrospective analysis of five patients with tdPD was performed who underwent DBS using a parietal approach. Changes in symptom severity, disease‐specific health‐related quality of life and l ‐dopa equivalent doses (LED) were evaluated over a total time course of 12 months. Results: DBS within both targets yielded significant improvement of parkinsonian symptoms (median: 40.0%, p = 0.04) in the first 6 months of continuous stimulation and remained stable thereafter (median improvement at 12 months: 43.2%, p = 0.07). Sustained improvement of tremor (median at 6 months: 100.0%, p = 0.04; median at 12 months 83.3%, p = 0.04) and quality of life scores (median at 6 months: 29.8%, p = 0.04; median at 12 months: 32.6%, p = 0.04) was noted throughout the follow‐up period. No significant change of LEDs was observed by the end of follow‐up (median decrease: 2.2%, p = 0.89). Conclusions: Simultaneous DBS of VIM and STN using one trajectory is safe, yielding good control of parkinsonian tremors. Further studies, however, are necessary to determine whether a parietal trajectory affords better control over tremor symptoms than established strategies and hence justifies the potential risks associated with the alternative approach.